Synthesis of new pyrrolidine-based organocatalysts and study of their use in the asymmetric Michael addition of aldehydes to nitroolefins - Castán, Alejandro; Badorrey, Ramón; Gálvez, José A.; Díaz-de-Villegas, María D. (Beilstein Journal of Organic Chemistry, 2017)
New pyrrolidine-based organocatalysts with a bulky substituent at C2 were synthesized from chiral imines derived from (R)-glyceraldehyde acetonide by diastereoselective allylation followed by a sequential hydrozirconation/iodination reaction. The new compounds were found to be effective organocatalysts for the Michael addition of aldehydes to nitroolefins and enantioselectivities up to 85% ee were achieved.
Keywords: enantioselective synthesis; Michael addition; organocatalysis; pyrrolidines; synthetic methods